Overlap Syndrome Involving Systemic Lupus Erythematosus and Autoimmune Hepatitis in Children: A Case Report and Literature Review - Lai, Wan-Tz; Cho, Wan-Hua; Eng, Hock-Liew; Kuo, Ming-Hui; Huang, Fu-Chen (Frontiers in Pediatrics, 2019)
Background: The diagnosis of overlap syndrome involving systemic lupus erythematosus (SLE) and autoimmune hepatitis (AIH) is not easily established because of its similar clinical presentations and biochemical features to those of lupus hepatitis. The term overlap syndrome is usually used in the context of overlap of autoimmune hepatitis with PSC (primary sclerosing cholangitis) or PBC (primary biliary cholangitis). Few cases of AIH complicated by SLE have been reported in the literature, and the condition is even rarer in childhood. Case presentation: Here we report the case of a 16-year-old girl with SLE who initially presented with autoimmune (cholestatic) hepatitis. According to American Association for the Study of Liver Diseases practice guidelines, the diagnosis was made based on aggregated scores including female (+2); ALP:AST (or ALT) ratio < 1.5(+2); elevated serum IgG level(+3); ANA > 1:80 (+3); negative hepatitis viral markers and drug history (+3, +1); average alcohol intake < 25 g/day (+2); and histological interface hepatitis features (+3). She then developed a malar rash, ANA positivity, anti-double-stranded DNA (anti-dsDNA) antibodies, and a low complement level. She met 4 of 17 Systemic Lupus International Collaborating Clinics classification criteria (1) for SLE. Our patient responded very well to corticosteroid at an initial dose of methylprednisolone 40 mg Q12H for 4 days tapering to 1 mg/kg/day according to liver function test results and bilirubin level. No relapse occurred during the 3-year follow-up course. Conclusions: Overlapping of SLE and AIH should be suspected when children with SLE have impaired liver function or AIH patients present with a malar or other skin rash. Liver biopsy plays an important role in establishing the differential diagnosis of SLE with liver impairment or overlap with AIH. The prompt diagnosis and adequate further treatment plans can improve disease outcomes.